2022
DOI: 10.1111/jce.15498
|View full text |Cite
|
Sign up to set email alerts
|

Grid‐mapping catheters versus PentaRay catheters for left atrial mapping on ensite precision mapping system

Abstract: Introduction: Areas displaying reduced bipolar voltage are defined as low-voltage areas (LVAs). Moreover, left atrial (LA) LVAs after pulmonary vein isolation (PVI) have been reported as a predictor of recurrent atrial fibrillation (AF). In this study, we compared grid mapping catheter (GMC) with PentaRay catheter (PC) for LA voltage mapping on Ensite Precision mapping system.Methods: Twenty-six consecutive patients with LVAs and border zone within the LA were enrolled. After achieving PVI, voltage mapping und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
(21 reference statements)
0
4
0
Order By: Relevance
“… 5 Saito et al . 23 also revealed that bipolar voltage amplitude estimated by Advisor HD Grid was significantly larger than PentaRay catheter. Similarly, smaller LVAs were seen using Advisor HD Grid when compared with either linear duodecapolar catheter 24 or CMC maps in the same patients.…”
Section: Discussionmentioning
confidence: 79%
“… 5 Saito et al . 23 also revealed that bipolar voltage amplitude estimated by Advisor HD Grid was significantly larger than PentaRay catheter. Similarly, smaller LVAs were seen using Advisor HD Grid when compared with either linear duodecapolar catheter 24 or CMC maps in the same patients.…”
Section: Discussionmentioning
confidence: 79%
“…Compared with coronary sinus pacing, the average amplitude during sinus rhythm was significantly higher, indicating the directional dependence of amplitude of bipolar signal [ 38 ]. Additionally, factors such as electrode spacing and size, degree of tissue contact, signal filtering (references selected), and number of mapping points can also affect the mapping results for LVA [ 39 ]. These could explain some of the discordant results between studies.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the mapping catheters we used were LASSO electrodes, which have relatively few mapping points, low mapping density, cannot be automatically mapped, and usually required manual correction. In recent years, many high-density and ultra-high-density mapping electrodes, such as PentaRay catheters, Orion catheters, and HD Grid catheters have been developed, and some are currently used in clinical applications ( 53 , 54 ). The Orion basket electrodes had high electrode density, with a total of 64 electrodes located in 8 basket branches.…”
Section: Discussionmentioning
confidence: 99%